A radar‐based rainfall climatology of Great Britain and Ireland. (May 2015) - Fairman, Jonathan G.; Schultz, David M.; Kirshbaum, Daniel J.; Gray, Suzanne L.; Barrett, Andrew I.
<x xml:space="preserve">Abstract</x> The Met Office 1km radar‐derived precipitation‐rate composite over 8 years (2006–2013) is examined to evaluate whether it provides an accurate representation of annual‐average precipitation over Great Britain and Ireland over long periods of time. The annual‐average precipitation from the radar composite is comparable with gauge measurements, with an average error of +23mmyr−1 over Great Britain and Ireland, +29mmyr−1 (3%) over the United Kingdom and –781mmyr−1 (46%) over the Republic of Ireland. The radar‐derived precipitation composite is useful over the United Kingdom including Northern Ireland, but not accurate over the Republic of Ireland, particularly in the south.